Clinical characteristics of metabolic associated fatty liver disease (MAFLD) in subjects with myotonic dystrophy type 1 (DM1). Issue 11 (November 2021) - Miele, Luca; Perna, Alessia; Dajko, Marianxhela; Zocco, Maria A.; De Magistris, Antonio; Nicoletti, Tommaso F.; Biolato, Marco; Marrone, Giuseppe; Liguori, Antonio; Maccora, Daria; Valenza, Venanzio; Rossi, Salvatore; et al.
Abstract: Background: Myotonic dystrophy type 1 (DM1) is a rare inherited neuromuscular disease associated with insulin resistance, and its association with metabolically associated fatty liver disease (MAFLD) has never been explored in prospective studies. The aim of this study was to assess the clinical features of MAFLD in DM1 patients. Methods: We investigated the prevalence and the diagnostic features of MAFLD in a cohort of 29 outpatient fully characterized DM1 patients; afterward, we compared the selected cohort of DM1-MAFLD individuals with a propensity-matched cohort of non-DM1-MAFLD Results: 13/29 (44.83%) DM1 patients received a clinical diagnosis of MAFLD. Compared to DM1 patients with normal liver, DM1-MAFLD individuals showed a higher male prevalence ( p  = 0.008), BMI ( p  = 0.014), HOMA score ( p  = 0.012), and GGT levels ( p  = 0.050). The statistical comparison showed that the DM1-MAFLD group had a more severe MAFLD according to the FIB4 score than non-DM1-MAFLD patients. This association of a more severe form of liver disease with DM1 remained significant after logistic regression analysis (OR: 6.12, 95% CI 1.44- 26.55).